1995
DOI: 10.3758/bf03206794
|View full text |Cite
|
Sign up to set email alerts
|

The role of visual attention in saccadic eye movements

Abstract: The relationship between saccadic eye movements and covert orienting of visual spatial attention was investigated in two experiments. Inthe first experiment, subjects were required to make a saccade to a specified location while also detecting a visual target presented just prior to the eye movement. Detection accuracy was highest when the location of the target coincided with the location of the saccade, suggesting that subjects use spatial attention in the programming and/or execution of saccadic eye movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
913
7
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,265 publications
(975 citation statements)
references
References 31 publications
50
913
7
5
Order By: Relevance
“…This is not surprising given that the parietal cortical areas mediating shifts of covert attention and eye movements overlap (Anderson et al, 1994;Corbetta et al, 1998) and that cognitive studies have also shown links between covert and overt attention (Hoffman, 1998;Klein, Kingstone, & Pontefract, 1992). Scinto et al found that individuals with AD were less accurate and slowed in shifting their gaze between a central fixation point and a target dot presented in sequence at peripheral locations.…”
Section: Attention Shiftingmentioning
confidence: 99%
“…This is not surprising given that the parietal cortical areas mediating shifts of covert attention and eye movements overlap (Anderson et al, 1994;Corbetta et al, 1998) and that cognitive studies have also shown links between covert and overt attention (Hoffman, 1998;Klein, Kingstone, & Pontefract, 1992). Scinto et al found that individuals with AD were less accurate and slowed in shifting their gaze between a central fixation point and a target dot presented in sequence at peripheral locations.…”
Section: Attention Shiftingmentioning
confidence: 99%
“…First, attention is directed toward the target of a saccade prior to saccade initiation (Hoffman and Subramanian, 1995). This enables the FEF to wrest attention away from physically prepotent stimuli and instead focus attention on a motivationally salient saccade target, by means of excitatory FEF-PPC projections ( Figure I).…”
Section: Interactions Bet\veenfi·ontal and Posterior Saccade Generatorsmentioning
confidence: 99%
“…Typically, saccades are preceded by covert shifts of visual attention to the target location (Deubel and Schneider 1996;Hoffman and Subramaniam 1995;Kowler et al 1995) and can enhance hearing performance at that location prior to the movement (Rorden and Driver 1999). In turn, shifts of covert attention were linked to saccade preparation (Kustov and Robinson 1996;Rizzolatti et al 1987Rizzolatti et al , 1994) but do not necessarily initiate saccades, i.e., we can attend to locations in the visual periphery without large eye movements.…”
Section: Introductionmentioning
confidence: 99%